+0  
 
+1
206
3
avatar+4690 

17 Help.

 Feb 12, 2018
 #1
avatar+3840 
+1

First, add 5 to both sides. then square both sides, and then expand, and solve. The answer should be \(-2\)

.
 Feb 12, 2018
 #2
avatar+557 
+1

explanation to tertre's answer

 

√2x+13 -5=x

+5               +5

√2x+13= x+5

2x+13=(x+5)^2

2x+13=(x+5)(x+5)

2x+13=x^2+5x+5x+25

2x+13=x^2+10x+25

2x=x^2+10x+25-13

2x=x^2+10x+12

x=x^2+10x+12/2

x=0.5x^2+5x+6

 

 

winkwinkwink

 Feb 12, 2018

11 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.